2021
DOI: 10.3390/microorganisms9102042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Secretomics Analysis Reveals the Major Components of Penicillium oxalicum 16 and Trichoderma reesei RUT-C30

Abstract: In this study, the major secretome components of Penicillium oxalicum 16 and Trichoderma reesei RUT-C30 under wheat bran (WB) and rice straw (RS) solid-state fermentation were systematically analyzed. The activities of the major components, e.g., cellulase, hemicellulase, and amylase, were consistent with their abundance in the secretomes. P. oxalicum 16 secreted more abundant glycoside hydrolases than T. reesei RUT-C30. The main up-regulated proteins from the induction of WB, compared with that from RS, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Wheat bran was used as carbon substrate for A. niger NS-2 and its appreciable yields of CMCase, FPA and β-glucosidase reached 310, 17 and 33 U/g dry substrate respectively (Bansal et al 2012 ). Wang et al ( 2021 ) systematically analyzed the major secretome components of T. reesei RUT-C30 under wheat bran solid-state fermentation and found that wheat bran induced more β-1,4-glucosidases than rice bran. Wheat bran was used as carbon source for solid fermentation of T. harzianum (Zhang and Yang 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wheat bran was used as carbon substrate for A. niger NS-2 and its appreciable yields of CMCase, FPA and β-glucosidase reached 310, 17 and 33 U/g dry substrate respectively (Bansal et al 2012 ). Wang et al ( 2021 ) systematically analyzed the major secretome components of T. reesei RUT-C30 under wheat bran solid-state fermentation and found that wheat bran induced more β-1,4-glucosidases than rice bran. Wheat bran was used as carbon source for solid fermentation of T. harzianum (Zhang and Yang 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus niger , the fungal transcriptomic response to sugar beet pulp was significantly different between solid culture and submerged culture, the latter inducing wider transcriptome variability [ 66 ]. Additionally, the fungal proteome and secretome complexity were affected by the cultivation modes in Aspergillus and Trichoderma species [ 67 , 68 , 69 ]. In Penicillium ubiquetum isolated from the blue mussel Mytilus edulis , it has been shown that, following the OSMAC approach, the culture performed on the seawater CYA (Czapek Yeast extract Agar) medium selectively enhances the production of some structurally related compounds [ 70 ].…”
Section: Discussionmentioning
confidence: 99%